ANALISIS DAN PERBANDINGAN SEGITIGA KERJA: TURBIN SUDU SETENGAH LINGKARAN, SUDU SEGITIGA DAN SUDU SIRIP UNTUK MENGHASILKAN RPM YANG TERTINGGI - Gregory Rama Darantiah Ruing; Antonius Ibi Weking; Lie Jasa (Jurnal SPEKTRUM, 2019)
At present the power plant has a high dependence on energy sources such as diesel, natural gas and coal, while its energy source in nature is increasingly scarce, this situation encourages the development of renewable energy, one of which is in micro hydro power plants. This study aims to determine the effect of the width of the work triangle on the highest rpm produced. the fall of water on the pinwheel is set from the position angle of the nozzle 00, 150, 300, 450, 600, 750 and from the angle of the nozzle 00, 50, 100, 150, 200, 250, 300, 350 and 400 on the semicircular blade turbine, triangle blade turbine , and fin blade turbines. Semicircular turbine blade, working triangle area produces greater rpm at position of angle nozzle 00 and angle of nozzle 250 with area of work triangle 360,36 cm2, where the position produces 216 rpm at windmill rotation and 1626 rpm at generator rotation. When the nozzle position angle 150 and the nozzle angle 200 with the working triangle area 264.27 cm2, produce 221 rpm at the pinwheel rotation and 1711 rpm at the generator rotation. while at the nozzle position angle of 300 and the angle of the nozzle 100 the area of the triangle works 134.37 cm2 and produces 173 rpm at the spinning wheel and 1307 rpm at the generator rotation. on the triangle blade turbine and fin blade, the working triangle area does not affect the rpm produced.